2016
DOI: 10.1111/eje.12199
|View full text |Cite
|
Sign up to set email alerts
|

Neither Basic Life Support knowledge nor self‐efficacy are predictive of skills among dental students

Abstract: Neither knowledge nor self-efficacy was predictive of BLS skills. Dental students had low levels of knowledge and skills in BLS. Despite this, their confidence in their ability to perform BLS was high and did not predict actual competence. There is a need for additional hands-on training, focusing on self-efficacy and BLS skills, particularly the use of AED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
4
0
3
Order By: Relevance
“…Although students who had received more than one BLS training scored higher (41.5% correct answers) than the students who had only had the mandatory class (39.5% mean correct answers), the difference in the scores was narrow and both showed a mean less than 50%, which was unsatisfactory these results are consistent with previous Saudi Arabian study, which has consistently found low BLS awareness [12], [13]. Furthermore, several countries have recorded low BLS awareness scores among health students [14]- [16].…”
Section: Discussionsupporting
confidence: 86%
“…Although students who had received more than one BLS training scored higher (41.5% correct answers) than the students who had only had the mandatory class (39.5% mean correct answers), the difference in the scores was narrow and both showed a mean less than 50%, which was unsatisfactory these results are consistent with previous Saudi Arabian study, which has consistently found low BLS awareness [12], [13]. Furthermore, several countries have recorded low BLS awareness scores among health students [14]- [16].…”
Section: Discussionsupporting
confidence: 86%
“…8 Poor BLS knowledge scores among health students have been reported in many countries. 9,[16][17][18][19][20] Perceived barriers to BLS competency-including a lack of adequate education (i.e. knowledge acquisition) and educational reinforcement (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, participants obtained a score between 0 and 10. Participants passed the MCQ when scoring ≥ 8, based on current examination practices of life support courses [ 15 , 23 ].…”
Section: Methodsmentioning
confidence: 99%